Peran Sekretariat Dewan Dalam Mendukung Fungsi Dewan Perwakilan Rakyat Daerah Labuhanbatu - Nurul Fazirah Harahap; Siti Aisyah (Jurnal Mirai Management, 2023)
The DPRD (Regional People's Representative Council) cannot carry out its duties, divide tasks and fulfill everything. Functioning means that the organization does not have the auspices of other people. In this case, employees participate in carrying out and executing the work. The Regional People's Representative Council Service Center was formed to support and carry out the activities of the Regional People's Representative Council and especially its staff. This means that the structure of the regional government knows that there is a management, among other things, formed from regional leaders and the regional People's Representative Council as partners. Among other things, participation means improving regional government within it. The implementation of regional autonomy discussed adheres to the principle of decentralization, the principle of sharing of powers, and the principle of co-administration. Some public administration tasks are regional in nature, some are managed in an organized manner and remain the responsibility of the state. This study examines the role of DPRD Secretariat staff in carrying out the sacred duties of its members, especially the functions of legislation, budgeting and supervision. Use qualitative research methods to better describe employee roles. The survey results show that employee discipline still needs to be improved. Keywords : DPRD Secretariat Staff and DPRD Functions